O voo do dragão : futebol profissional, elites sergipanas e a Associação Desportiva Confiança - Medrado, Thomas Hudson Silva (2020)
The present work investigates the process of professionalization of Sergipe football in the light of the sociology of professions. It seeks to demonstrate the factors that build the professional field of football through two perspectives: first, attention to the relationship between state and sport; secondly, by the career study. The work has as a temporal frame based within three moments: the emergence of football in Sergipe, "professionalization" in 1960, and modernization starting in 2010. Therefore, it is divided into three stages. The first deals with the bibliographic review of the theoretical horizon of the research. The second consists of documentary research for analysis of the period between 1907 and 1960. The third stage is to conduct interviews with players in the under-20 category of the Associação Desportiva Confiança. The documentary review shows the relations between football and the state's agricultural elites in the state of Sergipe, revealing how internal conflicts in the sports field of football were associated with the disputes of influential local groups. Key figures in the construction of Sergipe's professional football participated in political conflicts at the same time. The interviews demonstrate how the codes and meanings produced within the sports field also directly influence their construction process. The Associação Desportiva Confiança incorporates and reproduces the new concepts that define a modern football, considering the physical structure of the club, training methods, new criteria for the selection of athletes, and incorporation of administrative methods. The research confirms that the construction of professional football in Sergipe takes place in an associated way, especially with: the state, local politics, and the economic sphere. Nevertheless, these external influences are not enough to describe its process. Professionalization also depends on the rules and codes internal to the field, as individuals consistently produce the meanings linked to the idea of "professional." Although the phenomenon of modernization is incipient in the Sergipe state, it is possible to demonstrate its influences and impacts through the Associação Desportiva Confiança.